Analysis of the Value of Character Education in the Folklore of Nan Sondang Ngilong-Ilong in Mandailing Natal - Hasibuan Nikmah Sari; Idawati Idawati; Khairunnisah Khairunnisah; Rukiah Rukiah (BIRCU, 2021)
This study aims to describe the value of character education contained in the folklore of Nan Sondang Ilong-Ilong. The data in this study are folk tales obtained from recording and written documentation. The method used in this research is descriptive analysis method. The data collection technique used is the note-taking technique. The results showed that the values of character education contained in the folklore of Nan Sondang Ilong-Ilong are very good for shaping human character from an early age. The value of character education contained in the folklore of Nan Sondang Ilong-Ilong can contribute to today's world because the value of character education contained in the folklore of Nan Sondang Ilong-Ilong is an educational value that is very close to everyday life so it is very suitable for instilled in oneself. In the folklore of Nan Sondang Ilong-Ilong, there are four values of character education, namely: the value of responsibility, hard work, mutual care, and compassion.